2020
DOI: 10.1521/pedi_2019_33_412
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Maternal Borderline Personality Disorder Features With Preschooler Executive Functioning and Theory of Mind

Abstract: Although children of mothers who have elevated borderline personality disorder (BPD) features are a high-risk group, there remains little research examining developmental mechanisms that place these offspring at risk for emerging psychopathology. The current study included 68 mother–preschooler dyads, in which mothers with elevated BPD features were oversampled. Preschoolers (aged 3 and 4 years) completed a battery of executive functioning (EF) and theory of mind (ToM) measures. Accounting for several covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Emotion knowledge was measured using an adapted version of the Affective Perspective Taking task (Denham, 1986;Pears & Moses, 2003;Zalewski, Musser, Binion, Lewis, & O'Brien, 2020). Prior to task initiation, children were shown four emotional faces (happy, sad, mad/angry, scared/afraid) and were instructed to identify all emotions both expressively, then receptively (by pointing).…”
Section: Child Emotion Regulation Domainsmentioning
confidence: 99%
“…Emotion knowledge was measured using an adapted version of the Affective Perspective Taking task (Denham, 1986;Pears & Moses, 2003;Zalewski, Musser, Binion, Lewis, & O'Brien, 2020). Prior to task initiation, children were shown four emotional faces (happy, sad, mad/angry, scared/afraid) and were instructed to identify all emotions both expressively, then receptively (by pointing).…”
Section: Child Emotion Regulation Domainsmentioning
confidence: 99%
“…BOR had correlations ≥.60 with several other PAI scales—including Aggression, Anxiety, Anxiety-Related Disorders, Depression, Paranoia, Schizophrenia, and Stress—in both samples. In addition, studies in our database reported that the PAI-BOR scale correlated .66 (Zalewski et al, 2020) and .69 (Dixon-Gordon & Laws, 2021) with depressive symptoms, and .60 with an indicator of internalizing psychopathology (Kerr et al, 2021).…”
Section: Comorbiditymentioning
confidence: 73%